2019
DOI: 10.1016/j.heliyon.2019.e02642
|View full text |Cite
|
Sign up to set email alerts
|

Association between olfactory sulcus morphology and olfactory functioning in schizophrenia and psychosis high-risk status

Abstract: Olfactory impairment has been reported in patients with schizophrenia and individuals with a high risk of psychosis, but its neural basis is largely unknown. We used magnetic resonance imaging to investigate the morphology of the olfactory sulcus (an indicator of olfactory system development) and its relation to olfactory function in 38 persons with an at-risk mental state (ARMS), 62 patients with schizophrenia, and 61 healthy controls. Odor detection and identification were examined with a T & T olfactometer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Based on the potential relationship between brain gyrification and local neuronal connectivity (Van Essen, 1997), the present results appear to be consistent with previous functional neuroimaging findings showing that the ARMS and Sz groups share local connectivity disruption involved in HG (Yoon et al, 2015;Du et al, 2018). A few MRI studies on cortical surface features in clinical high-risk individuals also showed similar gross morphological characteristics, such as altered sulcogyral patterns (Sasabayashi et al, 2017;Nakamura et al, 2019) and sulcaldepth abnormalities (Takahashi et al, 2019b), with patients with established Sz. In contrast to the evidence of active gray matter reductions in the superior temporal plane (e.g., HG and planum temporale) during the early illness stages of psychosis (Takahashi and Suzuki, 2018), a recent longitudinal study demonstrated the stability of gyrification features during the clinical high-risk period as a marker of early neurodevelopmental insults (Damme et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the potential relationship between brain gyrification and local neuronal connectivity (Van Essen, 1997), the present results appear to be consistent with previous functional neuroimaging findings showing that the ARMS and Sz groups share local connectivity disruption involved in HG (Yoon et al, 2015;Du et al, 2018). A few MRI studies on cortical surface features in clinical high-risk individuals also showed similar gross morphological characteristics, such as altered sulcogyral patterns (Sasabayashi et al, 2017;Nakamura et al, 2019) and sulcaldepth abnormalities (Takahashi et al, 2019b), with patients with established Sz. In contrast to the evidence of active gray matter reductions in the superior temporal plane (e.g., HG and planum temporale) during the early illness stages of psychosis (Takahashi and Suzuki, 2018), a recent longitudinal study demonstrated the stability of gyrification features during the clinical high-risk period as a marker of early neurodevelopmental insults (Damme et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The OFC presents three qualitatively distinct sulcal patterns based on the continuity of the medial orbital sulci (MOS) and lateral orbital sulci (LOS): in Type I, caudal and rostral portions of the LOS are connected, while the MOS are interrupted between caudal and rostral portions of MOS; in Type II, caudal and rostral portions of both the LOS and MOS are connected and continuous LOS and MOS are jointed by the horizontally oriented transverse orbital sulcus (TOS); in Type III, caudal and rostral portions of both LOS and MOS are interrupted (Chiavaras and Petrides, 2000). Unusual sulcal pattern distributions of OFC have been repeatedly reported in patients with established schizophrenia (Nakamura et al, 2007(Nakamura et al, , 2020Isomura et al, 2017), including in prodromal stage (Nakamura et al, 2019;Takahashi et al, 2019). OFC sulcal pattern is associated with socioeconomic status, cognitive function, symptom severity and impulsivity (Nakamura et al, 2007).…”
Section: Schizophreniamentioning
confidence: 99%
“…SCZ patients as well as FRs exhibited lower olfactory bulb volumes than HCs (Nguyen et al, 2011;Takahashi et al, 2019;Turetsky et al, 2003). Furthermore, the olfactory sulcus, an indicator of olfactory system development, which is associated with odor identification ability, was shallower bilaterally in ARMS and SCZ patients than in HCs (Takahashi et al, 2019). These structural abnormalities might be responsible for olfactory impairments in SCZ patients, individuals with ARMS and FRs.…”
Section: Correlations Between Olfactory Identification Ability and Cl...mentioning
confidence: 88%
“…The intermediate stria was the smallest and projected superiorly to meet the anterior olfactory nucleus near the olfactory trigone. Abnormalities in the olfactory bulb and olfactory-related brain structures, including the frontal and temporal cortices and subcortical structures, have been reported in SCZ patients and FRs (Masaoka et al, 2020; Nguyen et al, 2011; Ohi et al, 2016, 2017, 2022a; Takahashi et al, 2019; Turetsky et al, 2003). SCZ patients as well as FRs exhibited lower olfactory bulb volumes than HCs (Nguyen et al, 2011; Takahashi et al, 2019; Turetsky et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation